Dye diazonium-modified multiwalled carbon nanotubes: Light harvesters for elastomeric optothermal actuators. (September 2018) - Bensghaïer, Asma; Forro, Klaudia; Seydou, Mahamadou; Lamouri, Aazdine; Mičušik, Matej; Omastová, Mária; Beji, Mohamed; Chehimi, Mohamed M.
Abstract: Novel elastomer/modified carbon nanotube nanocomposites were prepared by melt mixing ethylene vinyl acetate (EVA) matrix with dye-grafted multiwalled carbon nanotubes (MWCNTs, CNTs in short). The latter were prepared by spontaneous reactions of diazotized Azure A (AA-N2 + ), Neutral Red (NR-N2 + ) and Congo Red (CR-N2 + ) dyes with CNTs in water at RT. The dispersion of the dye-modified CNTs was facilitated with cholesteryl 1-pyrenecarboxylate (PyChol) surfactant. The EVA/modified CNT nanocomposites were employed as optothermal actuators. The photo-actuation measurements were performed on the un-stretched as well as the stretched strips of pristine EVA and EVA/CNT-dye nanocomposites using a dynamic mechanical analyzer (DMA) equipped with a red light emitting diode (red LED) at a wavelength of 627 nm illuminated either 10 s or 30 s. The concentration of modified dyes, the use of PyChol surfactant and the applied pre-strain were the parameters investigated in this work. To sum up, the nanocomposites prepared so far could be regarded as promising optothermal actuators used for touch displays visually impaired people. Highlights: Dye-grafted CNT hybrids were prepared through diazonium chemistry. The hybrids are remarkable light harvesters. Elastomer/CNT-Dye nanocomposites respond to light and exhibit optothermal behavior. Elastomer/CNT-Dye nanocomposite thin films are highly promising optothermal actuators.